Urgensi pelatihan public speaking guna meningkatkan kepercayaan diri dan keterampilan berbicara di TPA Dusun Jetis Desa Sidomulyo - Mubarok, Samsul; Sholichah, Lilis; Anggraeni, Novika Fitri; Syarief, Muh Alima’sum; Setyaningsih, Wahyu (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Public speaking or public speaking skills are very beneficial for children in self-development. However, many children feel inadequate or unable to speak in public because they lack confidence, do not master the material, or do not understand how to do it. Children's public speaking skills must be nurtured, trained and developed continuously. These conditions became the basis for implementing the Real Work Study Program (KKN), namely public speaking training, attended by children in Jetis Hamlet, Sidomulyo Village. This service aims to build confidence in speaking in public, understanding the material to be presented, and applying public speaking techniques. Training is carried out during the service period. This training was carried out at the TPA. During the training, participants will receive primary material, public speaking techniques, and direct practice. The method used in this service is Participationology. Implementation starts from the initial observation stage, orientation, introduction to material, and practice, and ends with evaluation. The results of the training were quite good, as proven at the last meeting; the participants had achieved adequate public speaking skills, Increased self-confidence, were able to present material well, and could apply public speaking techniques.